cooperatives and social Economy - A Bayat (تعاون و کشاورزی, 2009)
cooperatives have become proper means for socio-economic development enhancing the interests of local communities through mutual aid.social Economy includes institutions،cooperatives،mutual entities ،unions and associations whose businesses have socio-economic nature.In view of the nature of cooperative societies it may be acknowledged that cooperatives are an example of socio-economic business.Any cooperative society includes as its purpose serving common needs of the members of the society. The needs might vary from accommodation and health services to production،employ ment and permanent income(with the last one،being typical to Canadian rural area).